Differences in proximal caries depth assessment between bitewing radiography and bisecting technique periapical radiography: Experimental study - Rahmadani, Shafira Wulan; Prasetyarini, Swasthi; Supriyadi, Supriyadi (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction:  Caries locations that are not easily accessible such as the proximal region of the tooth will be difficult to examine clinically so that radiographic examination can be used. Intraoral radiographs used in dentistry are periapical radiographs and bitewing radiographs. In periapical radiography can be done with two retrieval techniques, namely with parallel and bisecting techniques. The purpose of this study was to determine the difference in the value of proximal caries depth between bitewing radiography and bisecting technique periapical radiography. Methods: The type of research used is true experimental research with post test only control design. This study used a sample of 20 teeth that were made carious. Carious teeth were radiographed with two different techniques, namely bitewing radiography and periapical radiography with bisecting technique. Measurement of caries depth on radiographs using the ImageJ application. Measurements were made on all radiograph results with both techniques whose results were converted into digital images. Caries depth is measured from the meeting point of the outer line and occlusal line of caries to the closest point of caries to the pulp horn using millimeters. Results: On bitewing radiographs, the smallest caries depth value was 2.872 mm and the largest was 4.692 mm, while on periapical radiographs the smallest value was 3.213 mm and the largest was 4.820 mm. Conclusion: Based on the results of the research that has been carried out, it can be concluded that there is a difference in the value of proximal caries depth between bitewing radiographic examination and periapical radiographic bisection technique.KEY WORDS: Proximal caries, bitewing radiograph, periapical radiograph, bisecting technique.Perbedaan penilaian kedalaman karies proksimal antara radiografi bitewing dan radiografi periapikal teknik bisekting: studi experimentalABSTRAKPendahuluan:  Lokasi karies yang tidak mudah dijangkau seperti daerah proksimal gigi akan sukar diperiksa secara klinis sehingga dapat menggunakan pemeriksaan radiografis. Radiografi intraoral yang digunakan dalam kedokteran gigi adalah radiografi periapikal dan radiografi bitewing. Pada radiografi periapikal dapat dilakukan dengan dua teknik pengambilan, yaitu dengan teknik paralel dan bisekting. Tujuan penelitian ini adalah Untuk mengetahui perbedaan nilai kedalaman karies proksimal antara radiografi bitewing dan radiografi periapikal teknik bisekting. Metode: Jenis penelitian yang digunakan yaitu penelitian true experimental dengan desain post test only control design. Penelitian ini menggunakan sampel sebanyak 20 gigi yang dibuat karies. Gigi yang karies dilakukan radiografi dengan dua teknik yang berbeda, yaitu radiografi bitewing dan radiografi periapikal dengan teknik bisekting. Pengukuran kedalaman karies pada radiograf menggunakan aplikasi ImageJ. Pengukuran dilakukan pada semua hasil radiograf dengan kedua teknik yang hasilnya diubah menjadi gambar digital. Kedalaman karies diukur dari dari titik pertemuan garis terluar dan garis oklusal karies sampai ke titik terdekat karies dengan tanduk pulpa menggunakan satuan milimeter. Hasil: Pada radiograf bitewing memiliki nilai kedalaman karies yang terkecil sebesar 2,872 mm dan terbesar 4,692 mm, sedangkan pada radiograf periapikal nilai terkecil sebesar 3,213 mm dan terbesar 4,820 mm. Simpulan: Berdasarkan hasil penelitian yang telah dilakukan, dapat disimpulkan bahwa terdapat perbedaan nilai kedalaman karies proksimal antara pemeriksaan radiografi bitewing dan radiografi periapikal teknik bisekting.KATA KUNCI: Karies proksimal, radiografi bitewing, radiografi periapikal, teknik bisekting.